2000
DOI: 10.1046/j.1365-2648.2000.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of health professional attitudes and patient perceptions on ‘inappropriate’ accident and emergency attendances. The implications for current minor injury service provision in England and Wales

Abstract: Increasing attendances in accident and emergency (A and E) departments in the United Kingdom have been attributed to a greater number of patients presenting with minor injuries. A and E staff believe this type of patient is suitable for primary care, and is 'inappropriate' for A and E management. Thus, A and E staff find 'inappropriate' attenders time-consuming and unrewarding, and are less motivated to help them, whilst 'inappropriate' patients believe they have attended the appropriate service for their medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 45 publications
(75 reference statements)
1
60
0
1
Order By: Relevance
“…Even one England nursing journal article pointed out that medical professionals often fail to recognize the discrepancy between medical personnel and patient perceptions of the severity of their conditions. [15] Thus, data regarding rates of inappropriate ED use are so variable because in the end, they really come down to show how the patient views the severity of his or her medical issue. [9,16] Moreover, studies have recognized that the perspectives of patients, who generally have little to no medical training or knowledge, are substantially different from the opinion of health care providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even one England nursing journal article pointed out that medical professionals often fail to recognize the discrepancy between medical personnel and patient perceptions of the severity of their conditions. [15] Thus, data regarding rates of inappropriate ED use are so variable because in the end, they really come down to show how the patient views the severity of his or her medical issue. [9,16] Moreover, studies have recognized that the perspectives of patients, who generally have little to no medical training or knowledge, are substantially different from the opinion of health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…[9,16] Moreover, studies have recognized that the perspectives of patients, who generally have little to no medical training or knowledge, are substantially different from the opinion of health care providers. [2,6,7,9,15] An analysis of the triage systems of identification of non-emergent versus emergent conditions revealed that most triage processes have poor sensitivities and specificities with regards to determining the two conditions. [17] With such errors among the medically trained, it is unreasonable to expect that patients would have the knowledge necessary to accurately "self-triage" themselves to the proper facility of care.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely the patients perceptions, ideas or concerns were studied (35,36). Former research elicits their need for information about the different tasks of the services, reorganisation and accessibility of primary care during out-of-hours and triage (37)(38)(39)(40)(41).…”
Section: Qualitative Studymentioning
confidence: 99%
“…Este fenómeno viene siendo estudiado de manera significativa desde la década de los 90 del siglo pasado hasta el presente, particularmente en Estados Unidos. (Driscoll, Vincent, Wilkinson, 1987;Liggins, 1993;Afialo et al, 1995;Gill, Riley, 1996;Gill, 1999;Sanders, 2000;Sarver, et al 2002;afial, et al, 2004;Howard, et al, 2005;Northington, Brice, Zou, 2005;Carret, Fassa, Domínguez, 2009). La mayor parte de los estudios han sido realizados en Estados Unidos debido a la naturaleza de su sistema sanitario, que carece de un sistema de salud universal, por lo que la mayoría de personas de escasos recursos se ve obligada a utilizar los servicios de urgencias hospitalarios porque carecen de otra fuente de atención o de un seguro privado de salud (Rust, et, al, 2008).…”
Section: Introductionunclassified